2011
DOI: 10.1177/0194599810393856
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Medicine in Otolaryngology, Part 2

Abstract: What is the current state of evidence-based medicine in otolaryngology? This question inquires about the state of our literature, our attitudes and capabilities, and our patients' desires. Thus, this installment of "Evidence-Based Medicine in Otolaryngology" focuses on these 3 topics. First, the authors consider the literature relative to benchmarks for study design. Second, the data regarding otolaryngologists' and other surgical specialists' attitudes and understanding of clinical data are discussed. Third, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Each article was assigned a quality ranking, using levels of evidence as described by Shin et al Two scales were selected for quality assessment: a modified Downs and Black (DB) Scale and the assessment of multiple systematic reviews (AMSTAR) scale . The DB scale is a 26‐item tool, chosen due to its robustness in evaluating nonrandomized methodologies, including cohort and case‐control studies .…”
Section: Methodsmentioning
confidence: 99%
“…Each article was assigned a quality ranking, using levels of evidence as described by Shin et al Two scales were selected for quality assessment: a modified Downs and Black (DB) Scale and the assessment of multiple systematic reviews (AMSTAR) scale . The DB scale is a 26‐item tool, chosen due to its robustness in evaluating nonrandomized methodologies, including cohort and case‐control studies .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it appears to be as much a problem with statistics as it is steroids. This becomes even more critical in current efforts to establish evidence‐based medicine guidelines for treatment of hearing and vestibular disorders (Shin et al, 2010, 2011; Stachler et al, 2012). If treatments outcomes are a factor in developing patient therapy protocols, and no evidence of efficacy can be demonstrated, then patient treatment cannot be justified.…”
Section: Misconceptions About Corticosteroid Therapy For Hearing and mentioning
confidence: 99%
“…[14] Fuchs et al indicated that demonstration of real-time live-surgery sessions for a large audience in which ENT specialists participating in scientific meetings, can actively attend, can be a 'privilege' in that televiewers and audience can acquire instantaneous knowledge and training. They also stressed that such meetings can be more frequently organized.…”
Section: Discussionmentioning
confidence: 99%